Pembatasan Upaya Hukum Peninjuan Kembali di Jerman dan di Indonesia - Dharma Setiawan Negara; Erwin Susilo; Khairul Umam Syamsuyar (CV Rewang Rencang, 2025)
Judicial review (PK) is an extraordinary legal effort that allows criminal cases to be reopened even though they already have permanent legal force (res judicata). This mechanism aims to correct judicial errors that can occur due to novum, judge's error, or conflicting decisions. However, in the Indonesian legal system, PK can only be submitted by the convict or his heirs, which has given rise to debate regarding limited access to justice. This study highlights the relevance and implications of these limitations and compares them with legal systems in other countries, such as Germany, which implements the Wiederaufnahme des Verfahrens mechanism in the Strafprozessordnung (StPO). Through comparative analysis, it was found that the Indonesian legal system still has normative ambiguity in determining the limits of judge error and the category of novum that can be used as the basis for a PK. This study proposes a reformulation of the PK concept that is more inclusive, by expanding the subjects who have the right to apply for a PK not only limited to the convict or his heirs, but also other parties who have legal interests. In addition, stricter regulations are needed regarding the limits of judge error and the validity of the novum, as implemented in Article 359 of the German StPO.